Improving cardiac monitoring in patients with early-stage breast cancer receiving cardiotoxic chemotherapy in a multidisciplinary cancer center. Issue 28 (1st October 2022) - DeLuna, Hannah; Velikov, Dmitriy; Patel, Hardik; Feld, Jamie; Robin, Jason; Rosenberg, Carol A.; Saha, Poornima
Abstract : 191 Background: Patients with early stage breast cancer commonly receive anthracycline and anti-Her2 directed therapies which can result in cardiotoxicity, making cardiac monitoring crucial. In 2018, our rate of obtaining a follow up echocardiogram in this patient population was 38%. Subsequently, use of myocardial strain imaging in conjunction with echocardiography became available at our institution, allowing for potential earlier detection of cardiac dysfunction. We aimed to increase utilization of strain imaging and rate of follow up echocardiogram monitoring to at least 50% in hopes of enhancing prevention efforts. Methods: We developed a standardized protocol for cardiac monitoring in patients receiving cardiotoxic chemotherapy. We provided education to staff and workflow modification to include standard orders for strain echocardiogram in all relevant chemotherapy plans. Chart review for Stage 1-3 breast cancer patients who received anthracycline or trastuzumab based therapy at our ambulatory cancer center from January 2019 to December 2021 was performed. Completion of follow up echocardiogram and rate of strain imaging before and after July 2020 was assessed, as this is when strain imaging became widely available. Results: Rates of obtaining baseline echocardiogram were excellent. Rates of strain echocardiogram use improved from 26.3% to 97.9% following July 2020. Follow up echocardiograms were obtained regularly in those receiving trastuzumab based therapy before and after July 2020 at rates of 91.8% and 87.5%. Rates of follow up echocardiograms in those receiving anthracycline-based therapy also improved to our goal of greater than 50%, but was lower than the trastuzumab group at 57%. However, assessment of follow up cardiac imaging in the 2021 treatment group is still ongoing. Conclusions: We successfully implemented a program to standardize cardiac monitoring in patients undergoing cardiotoxic chemotherapy for breast cancer at our institution. We anticipate this will enhance detection of cardiotoxicity and utilization of consultative cardio-oncology services. Additional efforts to improve follow up cardiac imaging through collaboration with our survivorship program are ongoing.Patients with Stage 1-3 breast cancer receiving cardiotoxic chemotherapy. Dates Regimen Total number of patients Strain echo n (%) Baseline echo n (%) Follow up echo n (%) Jan 2019 – June 2020 Anthracycline 78 25 (32.1%) 78 (100%) 45 (57.7%) Trastuzumab 97 21 (21.6%) 97 (100%) 89 (91.8%) July 2020 – Dec 2021 Anthracycline 76 75 (98.7%) 76 (100%) 44 (57.9%) Trastuzumab 65 63 (96.9%) 64 (98.5%) 57 (87.5%)